2019
DOI: 10.1101/818625
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conserved bacterial genomes from two geographically distinct peritidal stromatolite formations shed light on potential functional guilds

Abstract: 13Stromatolites are complex microbial mats that form lithified layers and ancient forms are 14 the oldest evidence of life on earth, dating back over 3.4 billion years. Their emergence 15 aligns with the oxygenation of the Earth's atmosphere and insight into these ancient 16 structures would shed light on the earliest days of Earth. Modern stromatolites are 17 relatively rare but may provide clues about the function and evolution of their ancient 18 counterparts. Previous studies have assessed microbial divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…A few model mat systems were used for comparison at both taxonomic and functional levels. These included hypersaline mats from Shark Bay (Australia) [66], marine mats from Highbourne Cay (Bahamas) [67] stromatolites from Cape Recife and Schoenmakerskop (South Africa) [68], oligotrophic mats from Cuatro Ciénagas (Mexico) [69], and two HAAL mats: a rare archaeal biofilm from Diamante lake [19] and the hypersaline mats from Socompa [18]. Functional analysis based on COG markers for carbon fixation confirmed the KEGG-based observations for BM and TM.…”
Section: Plos Onementioning
confidence: 54%
“…A few model mat systems were used for comparison at both taxonomic and functional levels. These included hypersaline mats from Shark Bay (Australia) [66], marine mats from Highbourne Cay (Bahamas) [67] stromatolites from Cape Recife and Schoenmakerskop (South Africa) [68], oligotrophic mats from Cuatro Ciénagas (Mexico) [69], and two HAAL mats: a rare archaeal biofilm from Diamante lake [19] and the hypersaline mats from Socompa [18]. Functional analysis based on COG markers for carbon fixation confirmed the KEGG-based observations for BM and TM.…”
Section: Plos Onementioning
confidence: 54%
“…With this approach, Automappa has been used in our group to manually curate 242 MAGs from fourteen metagenomic samples across a diverse range of environments, including stromatolites, marine sponges and beetles which have been successfully published in scientific literature [8,[27][28][29]. Moreover, this tool has been used to produce an additional 376 final clusters from 13 more unpublished metagenomes derived from a similar diverse range of environments.…”
Section: Resultsmentioning
confidence: 99%
“…Automappa assisted in gaining these insights by enabling expert curation of metabolic pathways respective to each of the Tethybacterales MAGs. Similarly, microbiomes from geographically distinct stromatolite formations were curated using Automappa allowing comparison of the conserved MAGs' functional gene sets recovered [28].…”
Section: Resultsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted August 20, 2023. ; https://doi.org/10.1101/2023.08.19.553462 doi: bioRxiv preprint reported in High-Bourne Cay (Khodadad & Foster, 2012). In Lake Magadi (Kambura et al, 2016) and Hamelin Pool (Ruvindy et al, 2015), only members of Euryarchaeota and TACK have been reported, whereas in Cape Recife (Waterworth et al, 2020), members of Asgard and DPANN have been reported. However, other analyses often report only the dominant relative abundance of some specific members of a single phylum, such as in Lake Tyrrel (Andrade et al, 2015), Euryarchaeota and Nanohaloarchaeota dominate in the Dead Sea (Jacob et al, 2017), and within the phylum Euryarchaeota, only members of of the family Halobacteriaceae.…”
Section: Discussionmentioning
confidence: 99%